Struktur, Lingkungan Penceritaan, dan Fungsi Mantra Pengobatan di Kelurahan Gates Kecamatan Lubuk Begalung Kota Padang - Yuliana; Yenni Hayati (Persona: Kajian Bahasa dan Sastra, 2022)
This study aims to describe: first the structure of the healing spell, the second the storytelling environment, the third function of the healing spell in Gates Village, Lubuk Begalung District, Padang City. This type of research is literary research using descriptive method. The data in this study are sentences that are healing spells in Gates Village, Lubuk Begalung District, Padang City. The data collected in this study were then analyzed by the following steps: (1) data collection stage, (2) data processing stage, (3) data classification or analysis stage, (4) conclusion stage of analysis results. There are three findings in this study. First, the structure of the spell is divided into three, namely opening, content, and closing. Second, the environment for telling the spell is divided into two main aspects, namely the aspects of supporting the reading of the mantra and the inheritance of the mantra. Third, based on function, found 4 functions of healing spells in the Gates Village. Based on these findings, it turns out that the healing mantra is still an oral literature that is highly trusted by the local community to treat diseases.